The Positive Effect of Perceived Exercise Benefit and the Negative Effect of Perceived Severity of Disease and Weakness on College Students' Amount of Exercise: The Mediate and Suppressor Role of Physical Fitness Evaluation Self-Efficacy - Xue-liu, Li; Mu, Xia (Frontiers in Psychology, 2021)
Background: The decline in the physical fitness of college students has become a serious social problem worldwide. Therefore, exploring the factors affecting the amount of exercise of college students is of great significance in improving college students' physique. According to the expectation value theory and previous studies, perceived exercise benefit and perceived severity of disease and weakness may have positive or negative impact on exercise behavior, and according to the self-efficacy theory, physical evaluation self-efficacy may be the most powerful motivational factors and it play a mediating role between other factors and exercise behavior. Therefore, this study was designed to determine the critical role of physical evaluation self-efficacy in the path of perceived exercise benefit and perceived severity of disease and weakness affecting the amount of exercise of college students. Methods: By means of Physical Fitness Health Belief of College Students Scale and Physical Activity Rating Scale (PARS-3), 801 undergraduate students were investigated in this study. Results: (1) when perceived exercise benefit, exercise self-efficacy, and severity of perceived disease and weakness predicted the amount of exercise separately, the first two have a positive effect on the amount of exercise, but the latter has no effect. However, when these three factors entered the regression equation at the same time, the perceived severity of disease and weakness had a negative effect on the amount of exercise. (2) the influence of physical evaluation self-efficacy on the college students' the amount of exercise was bigger than benefit of perceived exercise and the perceived severity of disease and weakness in both separated and simultaneous comparison conditions. (3) physical evaluation self-efficacy completely mediated the positive effect of perceived exercise benefits on the amount of exercise and inhibited the negative effect of perceived severity of disease and weakness on the amount of exercise. Conclusion: physical evaluation self-efficacy has a strong predictive power on the amount of exercise of college students. This was reflected in its ability to mediate the impact of expectation of exercise results and in its ability to suppress the adverse effects of concern about illness on exercise.